(untitled) (Minerva. Revista de Filología Clásica, 2019)
In this paper the author examines the singular classification of the dictio in three classes made by the XVth-century Spanish grammarian Juan de Pastrana in his Compendium grammaticae. Moreover, possible influences for such a classification are looked for in logical and grammatical tradition. Finally, this tripartite division is related to the similar ones carried out by Ramus and Sanctius in the XVIth century.